Tinggalan Arkeologis Situs Cariu Kecamatan Sukadana Kabupaten Ciamis - Ahmad Rizky Fauzi; Yulia Sofiani (Universitas Galuh, 2023)
This study aims to describe the archaeological remains of the Cariu Site in Sukadana District, Ciamis Regency which has the potential as a historical and cultural educational tourist attraction. Data was collected through observation and interview techniques that utilized field notes and an interview guide in the form of a list of questions for informants. Data analysis was carried out by triangulation through techniques of comparing, looking at sequences, and simultaneously examining cause-and-effect relationships. Based on the results of observations, it can be concluded that the Cariu Site which consists of the Mount Cariu area, the Cariu Girang Tomb, the Cariu Hilir Tomb, the Paneresan area, and the Pasir Pantun area has archaeological and historical remains in the form of cultural objects and historical texts. These remains are cross-sectional in nature and have educational, recreational, and economic values, so they are appropriate to be developed as educational tourism objects. The use of the Cariu site as an educational tourist attraction can not only provide economic value to the community and the government but also preserve the site as a cultural heritage in accordance with archaeological and historical concepts.